Cigarette smoking, problem-gambling severity, and health behaviors in high-school students. (June 2015) - Weinberger, Andrea H.; Franco, Christine A.; Hoff, Rani A.; Pilver, Corey; Steinberg, Marvin A.; Rugle, Loreen; Wampler, Jeremy; Cavallo, Dana A.; Krishnan-Sarin, Suchitra; Potenza, Marc N.
Abstract: Introduction: Smoking and gambling are two significant public health concerns. Little is known about the association of smoking and gambling in adolescents. The current study of high-school adolescents examined: (1) smoking behavior by problem-gambling severity and (2) health-related variables by problem-gambling severity and smoking status. Methods: Analyses utilized survey data from 1591 Connecticut high-school students. Adolescents were classified by problem-gambling severity (Low-Risk Gambling [LRG], At-Risk/Problem Gambling [ARPG]) and smoking status (current smoker, non-smoker). Analyses examined the smoking behavior of ARPG versus LRG adolescents as well as the smoking-by-problem-gambling-severity interactions for health and well-being measures (e.g., grades, substance use). Chi-square and logistic regression analyses were used; the latter controlled for gender, race/ethnicity, school grade, and family structure. Results: More adolescents with ARPG than LRG reported regular smoking, heavy smoking, early smoking onset, no smoking quit attempts, and parental approval of smoking. ARPG and LRG adolescents who smoked were more likely to report poor grades, lifetime use of marijuana and other drugs, current heavy alcohol use, current caffeine use, depression, and aggressive behaviors and less likely to report participation in extracurricular activities. The association between not participating in extracurricular activities and smoking was statistically stronger in the LRG compared to the ARPG groups. Post-hoc analyses implicated a range of extracurricular activities including team sports, school clubs, and church activities. Conclusions: Smoking was associated with poorer health-related behaviors in both ARPG and LRG groups. Interventions with adolescents may benefit from targeting both smoking and gambling. Highlights: We examined adolescent health behaviors by smoking status and gambling severity. Smoking was associated with poorer health behaviors for adolescent gamblers. Considering smoking may be helpful in interventions with adolescent gamblers.